PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT TERHADAP HASIL BELAJAR KOGNITIF SISWA MATERI JENIS-JENIS USAHA DAN KEGIATAN EKONOMI DI INDONESIA KELAS V SD - Saputra, Fredi Chandra (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2019)
Conventional learning has not been able to achieve its educational goals maximum. This is the low cognitive learning outcomes that students have. Research quasi-experimental design with Nonequivalent Control Group Design. Aim to determine the effect of the NHT learning model on cognitive learning outcomes Class V on the subject of types of business and activities economy in Indonesia. The fifth grade students of consist of 3 classes as its population. The results of sample selection using purposive sampling technique are two classes, namely class V.a as an experimental class with a total of 20 students, and class V.b as a control class with a total of 20 students. Collection techniques data by providing pre-test and post-test student cognitive learning outcomes. Data analyzed using the t-test, to determine the average equation and increase in student cognitive learning outcomes. The pre-test mean equation test results earned value . This shows that there is the equation of the average initial ability of students between the experimental group and control group. Hypothesis test obtained value, as well shows an increase in student cognitive learning outcomes taught through the model NHT learning is better than taught by learning conventional. So it is concluded that the type of cooperative learning model Numbered Head Together (NHT) has a good effect on learning outcomes cognitive students in the material types of business and economic activities in Indonesia at class V.